AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN BELUNTAS (Pluchea indica L.) ETANOL 70% DAN ETIL ASETAT MENGGUNAKAN DPPH - Asih Imulda Hari Purwani; Fita Sari; Muhammad Dhika Ramadhan; Herlinda Mawardika (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Pluchea indica L. is a herbaceous plant of the Asteraceae family that has been known to the public as fresh vegetables and traditional medicine since ancient times. This study aims to determine the antioxidant activity of beluntas leaves obtained from the extraction using 70% ethanol and ethyl acetate. The identification of phytochemical screening of beluntas leaves revealed the presence of flavonoids, tanninsand alkaloids. The test of antioxidant activity was performed using the DPPH method as free radical and vitamin C as a comparison. The average IC50 value beluntas leaves in 70% ethanol solvent is 94.06 ppm, in ethyl acetate is